Battlestar Galactica : Season 1 Disc 4 - Rod Hardy; Callis, James; Jamie Bamber; Katee Sackhoff; Mary McDonnell; Tricia Helfer; Edward James Olmos (USA UK Universal Studios, 2004)
The second war against the Cylons is over and The Twelve Colonies have been destroyed. Now Commander Adama of the Battlestar Galatica and President Laura Roslin lead a ragtag fleet of refugees in a supposed search for the fabled lost thirteenth colony, Earth. However, the dangers they face are many which compound an already difficult situation. In addition to The Cylons hunting and attacking the fleet in space; their infiltrator units carry out a more subtle plot even as their former unwitting pawn, Gaius Baltar, helps in the hunt for them while hiding both his own guilt and the strange presence that haunts his every thought. If that wasn't enough, the fleet also faces internal political conflict of which the rabble rousing figure, Tom Zarek, is merely the loudest dissenting voice. In the midst of these trials however, clues begin to appear that suggest that Adama's simple bluff about Earth may be more truthful than anyone knowing could have guessed.
After losing the war against the Cylon robots, the Battlestar Galactica crew speed toward the fabled 13th colony, Earth. Galactica Commander Adama (Olmos) and President Laura Roslin (McDonnell) face waning supplies, crushed morale, ... and the credible threat Cylons aboard the ship.
Language: English
Subtitle: English
Keywords: Adventure; Drama; SciFi; Action -- Tv Series